memperdalam, menjelaskan Tradisi Pembacaan Ratib al-Haddad di Pondok Pesantren Salafiyah Syafi'iyah Sukorejo-Situbondo: Pendekatan Fenomenologi terhadap Makna dan Pengalaman Santri - Halida; M. Samsul Hady; M. Lutfi Mustofa (Ulumuna: Jurnal Studi Keilsman, 2025)
This study examines the tradition of reading Ratib al-Haddad at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School, Situbondo, which has become an integral part of the spiritual and social life of students. Ratib al-Haddad, which consists of dhikr and prayers compiled by Imam Abdullah bin Alawi al-Haddad, serves as a means of getting closer to Allah and strengthening brotherhood between students. This reading not only has a spiritual, but also social dimension, contributing to the development of students' character, such as discipline, patience, and a sense of togetherness. This study uses a qualitative approach with a phenomenological method to reveal the subjective meaning of the reading of Ratib al-Haddad for students, as well as how this tradition functions as a da'wah medium that transcends the boundaries of pesantren and becomes part of the religious life of the community. The results of the study show that the recitation of Ratib al-Haddad not only strengthens faith and spirituality, but also strengthens solidarity among students and strengthens social ties in the pesantren environment